Current situation of small and medium-sized industrial enterprises in Trinidad & Tobago, Barbados and St. Lucia - Harris, Michael (ECLAC SantiagoCL, 2000)
Analyses the period 1990 to 1996 of the current situation of the small and medium-sized industrial enterprises (SMIs) in Trinidad and Tobago, Barbados and St. Lucia. Describes the evolution of SMIs, the country experiences regarding linkages amongst firms and the policy instruments aimed at promoting SMIs and their impact.